Effect of sugarcane genotypes and 2, 4-dichlorophenoxy acetic acid on callus induction - Subedi, M.; Ojha, B. R.; Ghimire, S. K.; Joshi, B. K.; Niroula, R. K.; Sah, B. P.; Chaudhary, R.; Kharel, R.; Poudel, A. P. (Journal of the Institute of Agriculture and Animal Science, 2018)
Callus induction is an important step in in-vitro culture valued for micropropagation, somaclonal variation, mutagenesis, synthetic seed production, transformation and genetic engineering. Callusing response of ten sugarcane genotypes viz., BO-110, BO-134, Cose-95422, Cose-98232, Cose-92423, UP-9742, BO-91, BO-135, and Cose-98255, were studied under three different doses (2, 3 & 4 mg L-1) of 2,4-D supplemented in the callus induction media. Callus induction was found to depend on both genotype and 2,4-D concentration in the media. The genotype UP-9742 was most amenable to callus induction (67.50%) followed by Cose-97182 (56.25%) and Cose-92423 (51.00%). While, the media supplemented with 3 mg L-1 2,4-D was found more effective to trigger callus induction in general. Yet, the optimum dose of 2,4-D to be used depends on the interaction of the specific genotype. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 237-242